Exploring previous studies related to teacher competence in planning individual education plans for students with special educational needs visual impairment - Nordin, Mohd Norazmi; Alwi, Shaliza; Abdul Wahab, Norwaliza; Mohd Noor, Nor Adila; Abd Ghani, Amirul Haqeem; Rosdi, Bella; Abbas, Mohd Saleh; Magiman, Mohamad Maulana (Pegem Akademi Yayincilik, 2024)
Competence is a combination of skills and knowledge in shaping one's identity to make something successful. Competent teachers need to prepare themselves with knowledge, skills and management in facing various challenges related to the implementation of national education goals. The interest, skills and preparation of teachers in providing educational services to students is very important in making their careers successful in shaping the desired students, including students with special needs (SEN). Teaching for MBPK can be carried out effectively if teachers have sufficient knowledge and skills and equip themselves with appropriate competence. Various studies from within and outside the country are conducted to explore issues related to teacher competence in planning and implementing effective teaching for students. Teacher's understanding and knowledge of the lesson content can make the teaching process run effectively. They stated that teachers who master the lesson content well can help them plan structured rooting strategies that can benefit students. Their study found that the skills and knowledge of teachers will create a learning atmosphere and better quality learning assessment.